2015
DOI: 10.1260/0958-305x.26.1-2.183
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration Study on the Large-Scale Battery Energy Storage for Renewables Integration

Abstract: The penetration level of the renewable energy resources has been expected to increase rapidly in several years as government has strongly encouraged those through various policies such as the RPS (Renewable Portfolio Standards) and feed-in tariffs. Because the performance of power system is sometimes critically constrained by stability characteristics, it is very challenging for system operator to realize such a high penetration of the renewable energy resources in power system. It has been proposed that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In order to solve the volume expansion, researchers proposed the following solutions. (1) Reducing the diffusion distance of the high ion diffusion energy barrier, reducing the black phosphorus, especially the grain size along the armchair, can improve rate performance. (2) Introduction of heteroatom doping and vacancies can, respectively, reduce their diffusion energy barrier or provide a new diffusion channel for lithium ions, and adjust the adsorption binding energy of lithium.…”
Section: The Mechanism Of Lithium/sodium Storagementioning
confidence: 99%
See 2 more Smart Citations
“…In order to solve the volume expansion, researchers proposed the following solutions. (1) Reducing the diffusion distance of the high ion diffusion energy barrier, reducing the black phosphorus, especially the grain size along the armchair, can improve rate performance. (2) Introduction of heteroatom doping and vacancies can, respectively, reduce their diffusion energy barrier or provide a new diffusion channel for lithium ions, and adjust the adsorption binding energy of lithium.…”
Section: The Mechanism Of Lithium/sodium Storagementioning
confidence: 99%
“…Very recently, N-doped blue phosphorus was also demonstrated to be a promising catalytic material in the cathode of LABs by DFT calculations based on the following characteristics [132]. (1) The blue phosphorus monolayer was stable during adsorption in the lithium-ion processes, contributing to sustaining a long-term electrochemical stability. (2) The low barrier energy of 0.11 eV along path 4 in Fig.…”
Section: Lithium-air Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of using battery systems in power grids first emerged in the 1980s. Notable examples since the 1980s are the BESS in Berlin, Lausanne, South Korea, Jeju Island, and other small island systems [133][134][135][136][137][138]. The integration of BESS in the power grid helps to solve many problems of the power grid [139][140][141][142][143].…”
Section: Technical Challengesmentioning
confidence: 99%
“…The idea of using battery energy storage systems (BESS) to cover primary control reserve in electricity grids first emerged in the 1980s. 25 Notable examples since have included BESS units in Berlin, 26 Lausanne, 27 Jeju Island in South Korea, 28 and other small island systems. 29,30 One review of realized or planned BESSs for ancillary service provision showed an average capacity of more than 4 MW h per BESS.…”
Section: Large-scale Bessmentioning
confidence: 99%